Achievement Emotion in Matemathics Learning: Meta-Regression - Zulkarnaen, Rafiq; Dewi Nur, Iyan Rosita (Department of Mathematics Education Program IPI Garut, 2024)
Penelitian yang mensintesis temuan empiris mengenai hubungan pencapaian emosi dengan hasil belajar matematika masih terbatas. Penelitian ini bertujuan untuk meninjau literatur dan melakukan meta-regresi mengenai pencapaian emosi terkait aktivitas (senang, marah, putus asa, dan bosan), emosi prospektif (cemas dan malu), dan emosi retrospektif (bangga) terhadap hasil belajar matematika. Pemahaman hubungan ini penting untuk mengoptimalkan proses pembelajaran matematika. Metode Systematic Literature Review dan meta-analisis (PRISMA) digunakan dalam penelitian ini. Dari hasil identifikasi, penyaringan, dan penilaian kelayakan, diperoleh 18 artikel yang dipublikasikan pada jurnal Database Scopus (Q1-Q4) antara tahun 2014 dan 2024. Sampel independen mencakup emosi marah (6 sampel, N = 4376), cemas (13 sampel, N = 10006), bosan (18 sampel, N = 11311), putus asa (6 sampel, N = 3423), malu (5 sampel, N = 2204), senang (19 sampel, N = 13536), dan bangga (8 sampel, N = 5003). Analisis meta-regresi dilakukan untuk menghitung ukuran efek setiap emosi terhadap hasil belajar matematika. Hasil penelitian menyimpulkan bahwa emosi marah, malu, putus asa, dan bosan menunjukkan efek sedang (0.3 ≤ |r| < 0.5) terhadap hasil belajar matematika, sedangkan emosi senang, cemas, dan bangga menunjukkan efek kuat (|r| ≥ 0.5). Temuan ini mengimplikasikan pentingnya pengendalian emosi dalam pembelajaran matematika untuk meningkatkan pencapaian akademik siswa.Limited research synthesizes empirical findings on the relationship between achievement emotions and mathematics learning outcomes. This study aims to review literature and conduct a meta-regression on achievement emotions related to activity emotions (joy, anger, hopelessness, and boredom), prospective emotions (anxiety and Embarassed), and retrospective emotions (pride) in mathematics learning outcomes. Understanding these relationships is crucial for optimizing mathematics learning processes. A Systematic Literature Review and meta-analysis (PRISMA) were employed. From identification, screening, and eligibility assessment, 18 articles published in Scopus Database journals (Q1-Q4) between 2014 and 2024 were obtained. Independent samples included anger (6 samples, N = 4376), anxiety (13 samples, N = 10006), boredom (18 samples, N = 11311), hopelessness (6 samples, N = 3423), Embarassed (5 samples, N = 2204), joy (19 samples, N = 13536), and pride (8 samples, N = 5003). Meta-regression analysis was conducted to calculate the effect size of each emotion on mathematics learning outcomes. The results concluded that anger, Embarassed, hopelessness, and boredom showed moderate effects (0.3 ≤ |r| < 0.5) on mathematics learning outcomes, while joy, anxiety, and pride exhibited strong effects (|r| ≥ 0.5). These findings imply the importance of emotion regulation in mathematics learning to enhance students' academic achievement.